The History of Islamic Political Thought: Shūrā, Social Justice, and Leadership from Classical to Modern Thinkers - Muhammad Ichsan; Desi Kurnia Sari; Elly Warnisyah Harahap (Medan Resource Center, 2026)
The historical development of Islamic political thought reflects the dynamic interaction between enduring religious principles and changing socio-political contexts. This article examines how the concepts of shūrā, social justice, and leadership have evolved in the works of six influential Muslim thinkers: Al-Farabi, Al-Mawardi, and Ibn Khaldun from the classical period, alongside Abul A'la Maududi, Ali Shariati, and Muhammad Iqbal from the modern era. Employing a qualitative literature-based approach, this study conducts a comparative analysis of primary and secondary sources to identify both continuity and change across different historical contexts. Unlike previous studies that primarily examine individual thinkers or specific periods, this article comparatively explores the historical development of these three political principles across classical and modern Islamic thought. The findings indicate that the core principles of Islamic political thought remain interconnected across contexts. Rather than representing a uniform transformation, the concepts of shūrā, social justice, and leadership demonstrate diverse reinterpretations in response to changing intellectual, political, and social circumstances. These findings underscore the historical adaptability of Islamic political thought while highlighting the significance of comparative historical analysis in understanding its continuing relevance to contemporary political discourse.